Antidepressant Activity of Methanolic Extract of Foeniculum Vulgare (Fennel) Fruits in Experimental Animal Models - Jamwal Neetu Singh, Kumar Sunil, Rana A.C (Journal of Applied Pharmaceutical Science, 2013)
The present study was undertaken to investigate the effects of methanolic extract of Foeniculum vulgare fruits (family: umbelifereae), popularly known as fennel, on depression using force swim test in rats, potentiation of norepinephrine toxicity in mice and haloperidol induce catalepsy in mice. The extract of F.vulgare (250 and 500 mg/kg) was administered orally to rats used in FST and 500mg/kg was administered in HIC and same dose administered in NE toxicity in mice. The dose of 250mg/kg and 500mg/kg of extract significantly (p
Keywords: Depression, Foeniculum vulgare, n